LA PRIMERA NORMATIVA TEATRAL DIECIOCHESCA PROMULGADA EN BUENOS AIRES: UN ANÁLISIS EN CLAVE COMPARADA. - BOTTA, MONICA (Dieciocho: Hispanic Enlightenment)
This essay traces the origins of the first theater regulations enacted in the Viceroyalty of River Plate in 1783. After establishing the historical context in which this regulatory framework emerged, this essay centers on the provisions that regulated dramatic censorship in the text of these regulations approved in Buenos Aires and in those governing the activity of the public theatres in Madrid during the same period. This comparative analysis allows us to highlight the points of convergence and divergence that existed between both regulations regarding the administration of the preventive censorship within the framework of the Enlightenment.